Application of Combined SEFT and SPEOS Therapy to Reduce Anxiety and Enhance Breast Milk Production in Postpartum Mothers: Literature Review (International Forum of Researchers and Lecturers, 2025)
The postpartum period is a critical stage marked by both physiological and psychological changes, one of which is anxiety. In Indonesia, postpartum anxiety affects 41–70% of mothers, interfering with the let-down reflex and resulting in decreased breast milk production. Meanwhile, the exclusive breastfeeding rate remains low at only 37.3% in 2023, far below the national target of 80%. This highlights the urgent need for non-pharmacological interventions that address both psychological and physiological aspects. This literature review explores the effectiveness of the Spiritual Emotional Freedom Technique (SEFT) and the Endorphin, Oxytocin, and Positive Suggestion Massage Stimulation (SPEOS) in reducing anxiety and enhancing breast milk production among postpartum mothers. Articles were searched from PubMed, ScienceDirect, Google Scholar, and DOAJ using keywords “SEFT,” “SPEOS,” “postpartum anxiety,” and “breast milk production,” applying relevance, inclusion–exclusion criteria, and methodological quality for studies published between 2017 and 2025. A total of 18 studies were selected, comprising quantitative and qualitative research, systematic reviews, and theoretical discussions. The analysis revealed that SEFT reduces anxiety through tapping on body meridian points combined with prayer and spiritual affirmations, which lower cortisol levels and induce relaxation. SPEOS, on the other hand, works through massage techniques that stimulate endorphin and oxytocin release, supported by positive suggestions that strengthen mothers’ confidence in breastfeeding, ultimately leading to improved milk production. Several studies reported that the combination of SEFT and SPEOS successfully reduced maternal anxiety while increasing breast milk volume by an average of 38.6 mL. These findings suggest that SEFT and SPEOS are effective, low-cost, and easy-to-implement non-pharmacological therapies for managing postpartum anxiety and optimizing breast milk production. Furthermore, their integration into community-based midwifery services could promote more holistic maternal care and support efforts to increase exclusive breastfeeding rates in Indonesia.